Recent Advances in Transition-Metal-Catalyzed Enantioconvergent Transformations of Epoxides - Li, Jianye; Li, Sijia; Liu, Shuting; Cui, Guohao; Zhang, Guozhu; Guo, Rui (Synthesis, 2024)
In recent years, asymmetric ring-opening reactions of epoxides have emerged as a compelling strategy for constructing chiral building blocks in organic synthesis. Among these, transition-metal-catalyzed stereoselective transformations of epoxides have garnered particular attention for their high efficiency and cost-effectiveness. The increasing interest and advancements in this area have spurred exploration into diverse transition-metal catalysts and chiral ligands, highlighting their potential to facilitate a wide range of transformations with enhanced efficiency and flexibility. This short review showcases significant achievements in transition-metal-catalyzed enantioconvergent transformations of epoxides, emphasizing their scope of application and reaction mechanisms.1 Introduction2 Palladium-Catalyzed Enantioconvergent Cross-Coupling of Epoxides3 Nickel-Catalyzed Enantioconvergent Cross-Coupling of Epoxides4 Titanium-Catalyzed Enantioconvergent Cross-Coupling of Epoxides5 Iridium-Catalyzed Enantioconvergent Cross-Coupling of Epoxides6 Cobalt-Catalyzed Enantioconvergent Cross-Coupling of Epoxides7 Copper-Catalyzed Enantioconvergent Cross-Coupling of Epoxides8 Conclusions and Outlook
Keywords: transition-metal-catalyzed; epoxides; enantioconvergent; cross-coupling; functionalization